Teologi Politik Martin Luther - Annette Aubert (VERBUM CHRISTI JURNAL TEOLOGI REFORMED INJILI, 2023)
This article examines Martin Luther’s political theology via his theological contributions to political discourses, reviewing select biblical commentaries, sermons, and catechism to identify important themes. In light of negative assessments of Luther’s political views, it is important to consult his theological and biblical texts when analyzing his ideas. To understand his presentation of a biblical political theology, it is important to comprehend how his biblical exegeses informed his political views. Luther differed from others in that his political ideas were principally theological; similar to Augustine, his political views were closely tied to aspects of theological anthropology and stressed the role of government as serving the common good and the welfare of the people. His understanding of political theology emphasized the gospel and freedom.